2012
DOI: 10.5194/amt-5-2403-2012
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative bias estimates for tropospheric NO<sub>2</sub> columns retrieved from SCIAMACHY, OMI, and GOME-2 using a common standard for East Asia

Abstract: Abstract. For the intercomparison of tropospheric nitrogen dioxide (NO 2 ) vertical column density (VCD) data from three different satellite sensors (SCIAMACHY, OMI, and GOME-2), we use a common standard to quantitatively evaluate the biases for the respective data sets. As the standard, a regression analysis using a single set of collocated ground-based Multi-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) observations at several sites in Japan and China from 2006-2011 is adopted. Examinations of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 19 publications
10
124
0
Order By: Relevance
“…There are now several stations worldwide providing observations from ground-based MAX-DOAS instruments (Hönninger et al, 2004;Irie et al, 2012;Kanaya et al, 2014;Hendrick et al, 2014), providing highly accurate measurements of tropospheric columns of various trace gases. Some of these stations now provide time series of 5 yr and more, thus allowing for a direct comparison of satellite-derived trends with trends obtained from a reliable reference source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are now several stations worldwide providing observations from ground-based MAX-DOAS instruments (Hönninger et al, 2004;Irie et al, 2012;Kanaya et al, 2014;Hendrick et al, 2014), providing highly accurate measurements of tropospheric columns of various trace gases. Some of these stations now provide time series of 5 yr and more, thus allowing for a direct comparison of satellite-derived trends with trends obtained from a reliable reference source.…”
Section: Discussionmentioning
confidence: 99%
“…NO 2 retrievals from SCIAMACHY have been validated in numerous studies, e.g., by Heue et al (2005) using airborne multi-axis differential optical absorption spectroscopy observations, by Boersma et al (2009) using in situ surface observations in Israel, and by Irie et al (2012) using inter-comparison techniques with NO 2 products derived from other satellite instruments as well as multi-axis differential optical absorption spectroscopy (MAX-DOAS) observations in Japan and China. The last one showed that SCIAMACHY-based tropospheric NO 2 columns were accurate with a −5 % bias and standard deviation of ±14 %.…”
Section: Satellite Datamentioning
confidence: 99%
“…Furthermore, MAX-DOAS systems are used for the validation of retrievals for reactive gases (e.g. Irie et al, 2012), whereas AERONET is widely used to validate satellite-derived aerosol optical depth (e.g. Schaap et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Tropospheric NO 2 column retrievals from satellites have been evaluated with in situ NO 2 profile measurements from aircraft (Heland et al, 2002;Martin et al, 2006;Boersma et al, 2008a;Bucsela et al, 2008Bucsela et al, , 2013Celarier et al, 2008;Hains et al, 2010), NO 2 column measurements from groundbased and airborne instruments Celarier et al, 2008;Brinksma et al, 2008;Kramer et al, 2008;Irie et al, 2008Irie et al, , 2012Wenig et al, 2008;Oetjen et al, 2013), in situ surface measurements (Schaub et al, 2006;Blond et al, 2007;Boersma et al, 2009;Lamsal et al, 2008Lamsal et al, , 2010, and a bottom-up NO x emission inventory (Lamsal et al, 2010). Aircraft offer precise in situ measurements within vertical spirals covering a spatial domain over a satellite field of view, but these are generally campaign-based experiments spanning only a few days to weeks and are limited by the need to extrapolate below the lowest measurement altitude (e.g.…”
Section: Introductionmentioning
confidence: 99%